Environmental Effects of Lower Zab Tributary on Benthic Invertebrates Species Diversity in Tigris River - Abdullah, S. A. H; Radhi, A. G; Abdul Jabbar, R.A (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Benthic   invertebrates'   diversity   and    some  physical    a:1dchemical characteristics in Lower Zab tributary and Tigris River were studied.  Month l y samples  were col l ected  from  November  2001 to October 2002.The rt:sLllts of the present study showed  the turbidity iu Tigris riverbefore the confluence to be higher (34.4 NTU) compared to the other stations.  Mean salinity was greater in Lower Zab tributary (0.33 %) compared to that in the river.  Lower Zab tJibutary and Tigris River were good in Oxygen content, and a high dissolved oxygen value was recorded (7.9 mg/L) in Lower Zab tributary.31  benthic invertebrate  species were identified, 14 of which werearthropods. 8 species from both of the Ol igochacta and Mollusca .One single  species  was  identi fled  from  the  Nemathelminthes.  Species diversity varied from 1.9 in Lower Zab tributary to 2.7 in Tigris River after  the  conll uence. The  h ighest  species  density  was recorded in Tigris River after the confluence was 359.1 indlnl  while the lowest species density was 12.74 ind/nl in Lower Zab tributary.